Biocontrol potential of Bacillus spp. against bacterial blight and bacterial leaf streak pathogens in rice - J Banluehan; Mattana Tunchai (International Journal of Agricultural Technology, 2025)
Bacterial leaf blight and bacterial leaf streak are major rice diseases caused by Xanthomonas oryzae pv. oryzae (Xoo) and X. oryzae pv. oryzicola (Xoc). In this study, rhizosphere soil samples were collected from healthy rice in Suphanburi, Kanchanaburi, and Surin provinces of Thailand. Among 135 bacterial strains isolated from the soil samples, only six isolates were selected mainly based on their strong antagonistic activity against Xoo. By dual-culture test, isolated strain KRI2 provided the largest Xoo inhibition zone diameters of 30.16 mm, followed by SRN19 and SPB1_1 with diameters of 24.30 mm and 24.06 mm, respectively. The largest Xoc inhibition zone diameter was obtained from strain SRN19 (15.46 mm), followed by strain SPB1_1 (14.21 mm) and strain SPB1_10 (14.00 mm). In addition, all six selected strains were able to inhibit the growth of Curvularia lunata, the rice pathogenic fungus. Morphological characterization revealed that all six strains were Gram-positive bacteria with rod shape. Molecular characterization by 16S rDNA gene sequencing analysis exhibited that all six strains belong to the genus Bacillus. Four isolated strains, SPB1_1, SPB1_10, SRN19, and KRI6, were identified as Bacillus velezensis. KRI2 and KRI4 were identified as Bacillus sonorensis and Bacillus subtilis, respectively. Besides, antagonist-related lytic enzyme production ability and plant growth-promoting traits of the six strains were observed. It was found that all six strains were able to produce protease and cellulase but showed an ability to solubilize phosphate and nitrogen fixation slightly.
Keywords: Plant-Microbe Interactions and Immunity; Plant Pathogenic Bacteria Studies; Legume Nitrogen Fixing Symbiosis